Martini 3: a general purpose force field for coarse-grained molecular dynamics - Souza, Paulo C T; Alessandri, Riccardo; Barnoud, Jonathan; Thallmair, Sebastian; Faustino, Ignacio; Grünewald, Fabian; Patmanidis, Ilias; Abdizadeh, Haleh; Bruininks, Bart M H; Wassenaar, Tsjerk A; Kroon, Peter C; Melcr, Josef; et al. (Nature methods, 2021)
The coarse-grained Martini force field is widely used in biomolecular simulations. Here we present the refined model, Martini 3 ( http://cgmartini.nl ), with an improved interaction balance, new bead types and expanded ability to include specific interactions representing, for example, hydrogen bonding and electronic polarizability. The updated model allows more accurate predictions of molecular packing and interactions in general, which is exemplified with a vast and diverse set of applications, ranging from oil/water partitioning and miscibility data to complex molecular systems, involving protein-protein and protein-lipid interactions and material science applications as ionic liquids and aedamers.
Keywords: Lipid Bilayers; termodynamika; Molecular Dynamics Simulation; lipidové dvojvrstvy; simulace molekulární dynamiky; vodíková vazba; Hydrogen Bonding; Thermodynamics